Rickettsia parkeri infection modulates the sialome and ovariome of the Gulf coast tick, Amblyomma maculatum - Guizzo, Melina Garcia; Budachetri, Khemraj; Adegoke, Abdulsalam; Ribeiro, Jose M. C.; Karim, Shahid (Frontiers in Microbiology, 2022)
The Gulf Coast tick, Amblyomma maculatum, is a vector of several tick-borne pathogens, including Rickettsia parkeri. The ability of R. parkeri to persist within the tick population through transovarial and transstadial transmission, without apparently harming the ticks, contributes to the pathogen’s perpetuation in the tick population. Previous studies have shown that the R.parkeri load in A. maculatum is regulated by the tick tissues' oxidant/antioxidant balance and the non-pathogenic tick microbiome. To obtain further insights into the interaction between tick and pathogen, we performed a bulk RNA-Seq for differential transcriptomic analysis of ovaries and salivary glands from R. parkeri-infected and uninfected ticks over the feeding course on a host. The most differentially expressed functional category was of bacterial origin, exhibiting a massive overexpression of bacterial transcripts in response to the R. parkeri infection. Candidatus Midichloria mitochondrii and bacteria from the genus Rickettsia were mainly responsible for the overexpression of bacterial transcripts. Host genes were also modulated in R. parkeri-infected tick organs. A similar number of host transcripts from all analyzed functional categories was negatively and positively modulated, revealing a global alteration of the A. maculatum transcriptome in response to pathogen infection. R. parkeri infection led to an increase in salivary transcripts involved in blood feeding success as well as a decrease in ovarian immune transcripts. We hypothesize that these transcriptional alterations facilitate pathogen persistence and transmission within tick population.